Function of metals and supports on the hydrodeoxygenation of phenolic compounds - Deepa, Ayillath K.; Dhepe, Paresh L. (ChemPlusChem, 2014)
Hydrodeoxygenation (HDO) is an important process for removing oxygen from lignin-derived phenolic monomers to obtain chemicals that can be used as fuel or fuel additives. A systematic study is performed to check the effects of supports (acidic, neutral, basic) and noble metals (Pd, Pt, Ru) on the HDO of phenol, guaiacol, and eugenol. Evaluation of the combinations of metals and supports under the similar reaction conditions shows that the metals supported on a highly acidic support (SiO2-Al2O3) yield complete hydrogenation products with the possibility of C[BOND]O bond cleavage to achieve a real HDO activity, whereas on a mildly acidic support (gamma-Al2O3), a complicated product distribution is achieved, and neutral (C) and basic (HT) supports give restricted hydrogenation activity but yield the products with very high selectivity. On the basis of the results, reaction pathways are suggested and deliberated. The catalysts show reproducible activity in recycle runs. The catalysts are characterized by various techniques (XRD, TEM, TPD, ICP-OES) to establish the catalyst activityproperty relationship.